Potential role of PM2.5 in melanogenesis. (November 2019) - Peng, Fen; Tsuji, Gaku; Zhang, Jian-zhong; Chen, Zhou; Furue, Masutaka
Abstract: Ambient particulate matter 2.5 (PM2.5 ) is one of the main components of air pollutants, which can absorb many polycyclic aromatic hydrocarbons and metals. The effect of PM2.5 on human skin and its biological significance in skin homeostasis remain incompletely understood. Previous studies demonstrated that PM2.5 can activate aryl hydrocarbon receptor (AhR), generate reactive oxygen species, and induce skin inflammation. These processes may be involved in melanocyte homeostasis and melanogenesis. We hypothesize that AhR signaling may be responsible for PM2.5 -related hyperpigmentation.